2011
DOI: 10.1016/j.infsof.2011.01.005
|View full text |Cite
|
Sign up to set email alerts
|

An experimental assessment of module documentation-based testing

Abstract: a b s t r a c tContext: Testing a module that has memory using the black-box approach has been found to be expensive and relatively ineffective. Instead, testing without knowledge of the specifications (white-box approach) may not be effective in showing whether a program has been properly implemented as stated in its specifications. We propose instead a grey-box approach called Module Documentation-based Testing or MD-Test, the heart of which is an automatic generation of the test oracle from the external and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
(62 reference statements)
0
5
0
1
Order By: Relevance
“…Therefore, it is impossible to explore the space of entire states with limited time resources and memories. SSP is a test case generation technique for modules [2][3][4]. The states are partitioned based on state's sensitivity towards events, conditions (pre-conditions) and actions (post-conditions).…”
Section: State-sensitivity Partitioning (Ssp)mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is impossible to explore the space of entire states with limited time resources and memories. SSP is a test case generation technique for modules [2][3][4]. The states are partitioned based on state's sensitivity towards events, conditions (pre-conditions) and actions (post-conditions).…”
Section: State-sensitivity Partitioning (Ssp)mentioning
confidence: 99%
“…Hence, a number of techniques were proposed for improving the effectiveness and efficiency of faults detection. State-sensitivity portioning (SSP) is one of them [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has experimentally been shown that mutation analysis can also be an accurate predictor of actual fault detection effectiveness of testing approaches [31]. On this regard, many researchers [38][39][40] have relied on applying mutation analysis as part of the experimental process to assess the effectiveness of different testing technqiues. Thus, we believe that the mutation analysis for measuring the fault detection effectiveness of the AOP testing approaches would be worthwhile and can provide experimental evidence in comparison with the conventional effectiveness analysis i.e.…”
Section: Context Selectionmentioning
confidence: 99%
“…Analysis the control flow functions logical relationship between the functions and get the function calling paths. It is different from the function relation of inclusion, the function contains relationship just analysis the function which contains, and does not consider the logical relationship [2] . FCP idea makes the basic path test workload exponentially reduced, making path oriented testpossible [3] .…”
Section: Introductionmentioning
confidence: 99%